Attraction of Halyomorpha halys (Hemiptera: Pentatomidae) haplotypes in North America and Europe to baited traps. Issue 1 (December 2017) - Morrison, William; Milonas, Panos; Kapantaidaki, Despoina; Cesari, Michele; Bella, Emanuele; Guidetti, Roberto; Haye, Tim; Maistrello, Lara; Moraglio, Silvia; Piemontese, Lucia; Pozzebon, Alberto; Ruocco, Giulia; et al.
Abstract Halyomorpha halys is a global invasive species, native to Southeast Asia, that is threatening agriculture in invaded regions. Our objectives were to: 1) establish the attractiveness of semiochemical stimuli paired with field-deployed traps in Europe (Greece, Hungary, Italy, and Switzerland), compared with Maryland, USA, and 2) identifyH. halys haplotypes recovered from traps at each location. We found qualitatively identical patterns of capture between sites located across Europe and in Maryland, USA. In both regions, captures ofH. halys adults indicated a synergistic response to traps baited with the two componentH. halys aggregation pheromone, and pheromone synergist, methyl (2E, 4E, 6Z )-decatrienoate when compared with either individually. Haplotype diversity in Europe based on trapped specimens was much greater than the USA, with five new haplotypes described here, probably indicating ongoing invasion and re-introduction ofH. halys . By contrast, a single, previously identified haplotype was trapped in Maryland, USA, representing a single introduction. AllH. halys haplotypes responded to each semiochemical in apparent proportion to their frequency in the overall population based on independently derived information from prior work. Taken together, these data suggest that pheromone-based technology will be of global utility for the monitoring of this important invasive species.